Inhibition of cell migration and induction of apoptosis by a novel class II histone deacetylase inhibitor, MCC2344. (October 2020) - Dawood, Mona; Fleischer, Edmond; Klinger, Anette; Bringmann, Gerhard; Shan, Letian; Efferth, Thomas
Graphical abstract: Highlights: Discovery of a cyclohexene carboxamide (MCC2344) out of 1162 ligands; it inhibits histone deacetylase 6 (HDAC6) activity. The newly identified agent MCC2344 binds directly to HDAC6 and shows collateral sensitivity towards CEM/ADR5000 cells. MCC2344 affects microtubule dynamics as observed by microarray analyses and immunofluorescence. HDAC6 inhibition by MCC2344 suppresses cell migration in the 2D and 3D cell culture, which eventually induces cell death. The importance of MCC2344 can be seen by its anti-tumor activity in vivo, in zebrafish. Abstract: Epigenetic modifiers provide a new target for the development of anti-cancer drugs. The eraser histone deacetylase 6 (HDAC6) is a class IIb histone deacetylase that targets various non-histone proteins such as transcription factors, nuclear receptors, cytoskeletal proteins, DNA repair proteins, and molecular chaperones. Therefore, it became an attractive target for cancer treatment. In this study, virtual screening was applied to the MicroCombiChem database with 1162 drug-like compounds to identify new HDAC6 inhibitors. Five compounds were tested in silico and in vitro as HDAC6 inhibitors. Both analyses revealed 1-cyclohexene-1-carboxamide, 2-hydroxy-4, 4-dimethyl -N- 1-naphthalenyl-6-oxo- (MCC2344) as the best HDAC6 inhibitor among the five ligands. The binding affinity of MCC2344 to HDAC6 was further confirmed by microscale thermophoresis. Additionally, the anti-cancer activity of MCC2344 was tested in several tumor cell lines. Leukemia cells were the most sensitive cells towards MCC2344, particularly the P-glycoprotein-overexpressing multidrug-resistant cell line CEM/ADR5000 exhibited remarkable collateral sensitivity towards MCC2344. Transcriptome analysis using microarray hybridization was performed for investigating downstream mechanisms of action of MCC2344 in leukemia cells. MCC2344 affected microtubule dynamics and suppressed cell migration in the wound healing assay as well as in a spheroid model by hyper-acetylation of tubulin and HSP-90. MCC2344 induced cell death in CEM/ADR5000 cells by activation of PARP, caspase-3, and p21 in addition to the downregulation of p62. MCC2344 significantly inhibited tumor growth in vivo in zebrafish larvae without mortality until 20 pM. We propose MCC2344 as a novel HDAC6 inhibitor for cancer treatment.